Genetic Signature of Acute Lymphoblastic Leukemia and Netherton Syndrome Co-incidence—First Report in the Literature - Skoczen, Szymon; Stepien, Konrad; Mlynarski, Wojciech; Centkowski, Piotr; Kwiecinska, Kinga; Korostynski, Michal; Piechota, Marcin; Wyrobek, Elzbieta; Moryl-Bujakowska, Angelina; Strojny, Wojciech; Rej, Magdalena; Kowalczyk, Jerzy; et al. (Frontiers in Oncology, 2020)
The aim of the following case report is to provide a description of acute lymphoblastic leukemia (ALL) in a patient with Netherton syndrome (NS). A 15-years-old male with NS was referred with suspicion of acute leukemia. Severe anemia, leukocytosis, thrombocytopenia and elevated CRP level were demonstrated in pre-hospital laboratory tests. Physical examination revealed generalized ichthyosiform erythroderma. ALL was diagnosed on the basis of bone marrow biopsy. The patient was initially classified as CNS3 status. No signals indicating fusion of BCR/ABL1, ETV6, RUNX1 genes and MLL gene rearrangement were found in the cytogenetic analysis. The patient was qualified for chemotherapy and treated according to ALL IC-BFM 2009 protocol for high-risk ALL. During induction therapy severe skin toxicity occurred (WHO grade III), which prompted the modification of treatment down to intermediate-risk strategy. In the course of reinduction therapy severe chemotherapy-induced adverse drug reactions occurred, including progression of skin toxicity to WHO grade IV. The patient achieved complete remission. In view of life-threatening toxicities and the confirmed complete remission, intensive chemotherapy regimen was discontinued and maintenance treatment was started. Because of the baseline CNS3 status the patient received cranial radiotherapy. Whole exome sequencing (WES) was used to identify disease-associated mutations. WES revealed two germline mutations: a novel premature termination variant in SPINK5 (p.Cys510*), along with a novel potentially pathogenic variant in NUP214 (p.Arg815Gln). Somatic mutations were: known pathogenic variants of JAK2 (p.Arg683Gly), IL17RC (p.Ala303Thr) and potentially pathogenic nonsynonymous variants of TTN (p.Gly1091Arg and p.Pro17245Leu), ACTN2 (p.Ile143Leu), TRPV3 (p.Arg729*) and COL7A1 (p.Glu2842fs) genes. Currently the patient continues maintenance chemotherapy, with stable status of skin lesions and no features of ALL relapse. To our knowledge, this is the first report of ALL in a patient with NS. As has been presented, in such patients optimal treatment according to the current protocols is extremely difficult. WES was used to confirm the diagnosis of Ph-like ALL in our patient. The detection of JAK2 gene mutation offers the possibility of therapy personalization. A specific signature of rare germline variants and somatic mutations can be proposed as a factor predisposing to the co-incidence of ALL and NS.